1991
DOI: 10.1055/s-2007-1024748
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Short Maximal Physical Exercise on Coagulation, Fibrinolysis, and Complement System

Abstract: In 11 healthy young subjects, the plasma concentrations of the thrombin-antithrombin III complex, fibrinopeptide A, tissue-plasminogen activator, complement fragments C3a and C4a, and histamine were measured before and after a graded maximal bicycle exercise test. The analyses were carried out 30 min before and immediately before exercise, immediately after exercise, and 30 and 60 min later. All post-exercise values were corrected for plasma volume changes, which were calculated from hematocrit and hemoglobin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
5
8

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 9 publications
10
39
5
8
Order By: Relevance
“…Some confusion is apparent in the literature regarding the post-exercise serum concentrations of immunoglobulins and complements which have been variously reported to remain unchanged, to decrease or to increase (35)(36)(37)(38). In the present study, the rate of change in C4 following the UEL was significantly lower in females than in males at Post-Camp.…”
Section: Discussioncontrasting
confidence: 61%
“…Some confusion is apparent in the literature regarding the post-exercise serum concentrations of immunoglobulins and complements which have been variously reported to remain unchanged, to decrease or to increase (35)(36)(37)(38). In the present study, the rate of change in C4 following the UEL was significantly lower in females than in males at Post-Camp.…”
Section: Discussioncontrasting
confidence: 61%
“…As for immunoglobulins and complements, there are many studies regarding exercise-mediated changes in these parameters, although the studies have presented conflicting results, showing increased, decreased or unchanged counts (32,(45)(46)(47). In the present study, one of the major reasons behind this mechanism may be the mobilization and recruitment of immunoglobulins and complements to the exercise-mediated denatured and damaged areas of muscle tissue, which had then entered the first inflammatory stage of the wound healing response.…”
Section: Discussioncontrasting
confidence: 49%
“…The increased level of plasma IL-2 observed 16 h after the marathon (Study I) has also been observed by Pedersen (1991). Complement activation has been observed after prolonged and short-term exercise (Dufaux et al 1989a(Dufaux et al , 1991Camus et al 1994). Small amounts of complement C5a have been found to induce chemotaxis, and enhance phagocytosis and enzyme release from human polynuclear neutrophils in vitro (Rimmer and Horton 1991).…”
Section: Discussionmentioning
confidence: 68%
“…By contrast, the literature is much less prolific on the acute phase reactant responses (Liesen et al 1977, Dufaux et al 1984, 1989a and b and 1991Camus et al 1994) and the metabolic implications (Blomstrand et al 1988;Poortmans et al 1991) involved during prolonged exercise. The present investigation is an attempt to make a link between the lymphocyte changes, some acute phase proteins and cytokine responses and some plasma metabolic implications.…”
Section: Discussionmentioning
confidence: 86%